Pre analytical Checklist: a relevant tool for External Quality Assessment (EQA) - Ventura, Catarina (2022)
According to ISO 15189 2012 laboratory shall participate in an external quality assessment (programme and implement the corrective actions when necessary The EQA programs should have the effect of checking the entire analytical process, including pre and post examination procedures The National Program for External Quality Assessment (provides since 2007 EQA pre analytical schemes, including a checklist since 2016. The aim of this work is to share PNAEQ’s checklist for pre analytical phase, and evaluate trend over time of the results of PNAEQ participants, between 2019-2021.